Do you have any pictures to choose from anything to show what im looking at?
The answer is 1 bc the solution is (1,-3)
Answer:
![y=-2x+2](https://tex.z-dn.net/?f=y%3D-2x%2B2)
Step-by-step explanation:
Hi there!
Slope-intercept form:
where m is the slope and b is the y-intercept (the value of y when the line crosses the y-axis)
<u>1) Determine the slope</u>
where the two given points are
and ![(x_2,y_2)](https://tex.z-dn.net/?f=%28x_2%2Cy_2%29)
Plug in the given points (-1, 4) and (0, 2)
![=\frac{2-4}{0-(-1)}\\=\frac{-2}{0+1}\\=\frac{-2}{1}\\= -2](https://tex.z-dn.net/?f=%3D%5Cfrac%7B2-4%7D%7B0-%28-1%29%7D%5C%5C%3D%5Cfrac%7B-2%7D%7B0%2B1%7D%5C%5C%3D%5Cfrac%7B-2%7D%7B1%7D%5C%5C%3D%20-2)
Therefore, the slope of the line is -2. Plug this into
:
![y=-2x+b](https://tex.z-dn.net/?f=y%3D-2x%2Bb)
<u>2) Determine the y-intercept</u>
![y=-2x+b](https://tex.z-dn.net/?f=y%3D-2x%2Bb)
Recall that the y-intercept is the value of y when the line crosses the y-axis, meaning that the y-intercept occurs when x is equal to 0.
One of the given points is (0,2). Notice how y=2 when x=0. Therefore, the y-intercept of the line is 2.
Plug this back into the equation:
![y=-2x+2](https://tex.z-dn.net/?f=y%3D-2x%2B2)
I hope this helps!
Answer:
4(2x-3)(2x + 3)
Step-by-step explanation:
Here, we want to simplify the given expression
we can have;
16x^2-36
= 4(4x^2 -9)
we can use the difference of two squares
where;
a^2 - b^2 = (a-b)(a + b)
= 4(2x-3)(2x+ 3)